Panganan Kasus Gagap Dewasa dengan Metode Fluency Shaping: Studi Kasus Tunggal - jumiarti, Jumiarti; Sazha Aathirah, Quamilla; Ningtyas (22013), Hestiana (Akademi Terapi Wicara, 2024)
A stuttere’s ability to produce speech fluently indicates of the success of a stuttering intervention. There is still little research related to the transfer of fluency to everyday situations, which is the reason for this research.